Upaya Meningkatkan Perilaku Organizational Citizenship Behavior (OCB) Pada Karyawan Pt. Pos Indonesia Persero Surakarta - Alean Kistiani Hegy Suryana; Milka Susana Theorupun (ProBank, 2018)
The purpose of this study was to analyze the Influence Emotional Intelligent and Work Motivation  on Organizational Citizenship Behavior (OCB)  with Job Satisfaction as a Mediating variable (Study at  employees PT. Pos Indonesia Persero Surakarta). This study used 168 employees of  PT. Pos Indonesia Persero Surakarta. The sampling technique was done by using probability sampling. In this study  a model of analysis was Regression Analysis with path analysis. Hypothesis Test Results show Emotional Intelligence has a significant effect on Job Satisfaction, Work Motivation has a significant effect on Job Satisfaction, Job Satisfaction has a significant effect on Organizational Citizenship Behavior, Emotional Intelligence has a significant effect on OCB, Work Motivation has a significant on OCB, Job Satisfaction mediates Emotional Intelligence towards OCB, Job Satisfaction mediates Work Motivation towards Organizational Citizenship Behavior (OCB). F test results are known the value of F = 125,764  significance of  0.000 <0.05, with the conclusion of the variables Emotional Intelligence, Work Motivation and Job Satisfaction have a significant effect on Organizational Citizenship Behavior (OCB). The total coefficient of determination (R2) of 0.798 can be interpreted as variation in OCB Employees at PT. Pos Indonesia Persero Surakarta explained by the variables Emotional Intelligence, Work Motivation and Job Satisfaction of 79.8% and the remaining 20.2% is explained by other variables outside the variables studied in this study.Keyword: Emotional Intelligent, Work Motivation,  Job Satisfaction, and Organizational Citizenship Behavior.